EFFECTIVENESS OF THE ISLAMIC COUNSELLING IN THE FORM OF PERSONALITY SOCIAL AFFAIRS STUDENT SMA 6 PADANGSIDIMPUAN - - ASMARYADI (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
This thesis entitled "The effectiveness of Islamic Counseling in Shaping Social Personality high school students in the country 6 Padangsidimpuan. Preparation of this paper is motivated importance of service orientation.Problems that exist in this thesis is how the Islamic counseling guidance and counseling teacher at the high school 6 Padangsidimpuan country. This study was conducted using instruments such test, questionnaire, interview and observation. Furthermore, the data were analyzed using SPSS statistical process and 20:00 The findings of this research are: 1) Score acquisition of Islamic counseling spread from the lowest value of 69.1 to a high of 85.5. From the calculation it is known that the average value and social personality is 29. By consulting the average value is determined on the classification assessment, the social personality in SMA 6 Padangsidimpuan in the category of "good" he replied. 2) Obtaining a score questionnaire on the character formation of students spread from a low 287 to a high of 480. The calculation is known that the average score and the character formation of students is 80.6. By consulting an average score on the classification assessment is set, then the formation of character formation of students in SMAN 6 Padangsidimpuan in the category "very good".Based on the above findings, it was concluded that the effectiveness of Islamic counseling in shaping the personality of students in SMAN 6 Padangsidimpuan can be said to be good. Similar studies should be done with a background of different contexts in order to compare the findings of this research.